Engineering and Economic Evaluation of The Production of Copper Nanoparticles (Cu-Nps) using Rongalite as Reducing Agent - Nia Purnamaningsih; Asep Bayu Dani Nandiyanto (KH. A. Wahab Hasbullah University, 2020)
The purpose of this study was to analyze the Economic Evaluation in the Production of Copper Nanoparticles (Cu-Nps) using Rongalite as Reducing Agent, an experimental method carried out in the perspective of engineering and economic evaluation. Technical analysis was performed using simple mass balance analysis, while economic evaluation was carried out using several economic parameters, including PBP, BEP, and CNPV. To support the analysis, all data is taken based on the available online shopping web. All calculations are carried out in ideal conditions for 20 years of production. Economic evaluation is carried out by giving 5 conditions (0%, 20%, 40%, 60%, and 80%) to the variable price variations in cost, sales, fixed cost, and labor. Economic evaluation analysis results show that price variations can affect the CNPV / TIC (%) curve to Life Time (year). In the variable cost, fixed cost, and labor variable price curve it is found that the condition of 0% is the highest curve compared to other conditions. While in sales price variations, the 80% condition is the highest curve. In conclusion, all price variation curves show profit. The benefits of this research are the large-scale economic evaluation data on Cu nanoparticle production.